On multichannel film dosimetry with channel‐independent perturbations. Issue 1 (17th December 2013) - Méndez, I.; Peterlin, P.; Hudej, R.; Strojnik, A.; Casar, B.
Abstract : Purpose: : Different multichannel methods for film dosimetry have been proposed in the literature. Two of them are the weighted mean method and the method put forth by Micke et al. ["Multichannel film dosimetry with nonuniformity correction, " Med. Phys. 38, – (2011)] and Mayer et al. ["Enhanced dosimetry procedures and assessment for EBT2 radiochromic film, " Med. Phys. 39, 2147–2155 (2012)]. The purpose of this work was to compare their results and to develop a generalized channel‐independent perturbations framework in which both methods enter as special cases. Methods: : Four models of channel‐independent perturbations were compared: weighted mean, Micke–Mayer method, uniform distribution, and truncated normal distribution. A closed‐form formula to calculate film doses and the associated type B uncertainty for all four models was deduced. To evaluate the models, film dose distributions were compared with planned and measured dose distributions. At the same time, several elements of the dosimetry process were compared: film type EBT2 versus EBT3, different waiting‐time windows, reflection mode versus transmission mode scanning, and planned versus measured dose distribution for film calibration and for γ‐index analysis. The methods and the models described in this study are publicly accessible through IRISEU. Alpha 1.1 (http://www.iriseu.com ). IRISEU. is a cloud computing web application for calibration and dosimetry of radiochromic films. Results: : The truncated normal distribution model provided the best agreement between film and reference doses, both for calibration and γ‐index verification, and proved itself superior to both the weighted mean model, which neglects correlations between the channels, and the Micke–Mayer model, whose accuracy depends on the properties of the sensitometric curves. With respect to the selection of dosimetry protocol, no significant differences were found between transmission and reflection mode scanning, between 75 ± 5 min and 20 ± 1 h waiting‐time windows or between employing EBT2 or EBT3 films. Significantly better results were obtained when a measured dose distribution was used instead of a planned one as reference for the calibration, and when a planned dose distribution was used instead of a measured one as evaluation for the γ‐analysis. Conclusions: : The truncated normal distribution model of channel‐independent perturbations was found superior to the other three models under comparison and the authors propose its use for multichannel dosimetry.